Intercorporeality: emerging socialities in interaction - Meyer, Christian; Streeck, Jürgen; Jordan, J. Scott (Oxford University Press, 2017)
" This book draws inspiration from Maurice Merleau-Ponty's concept of intercorporeality to offer a new, multidisciplinary perspective on the body. By drawing attention to the body's ability to simultaneously sense and be sensed, Merleau-Ponty transcends the object-subject divide and describes how bodies are about, into, and within other bodies. Such inherent relationality constitutes the essence of intercorporeality, and the chapters in this book examine such relationality from a host of diverse perspectives. The book begins with an introductory chapter in which the editors review the current research on bodily interaction, and introduce the notion of intercorporeality as a potentially integrative framework. The first section then offers four chapters devoted to clarifying theoretical and developmental perspectives on intercorporeality. Section 2 contains three chapters that provide insight on intercorporeality from evolutionary, historical, and cross-sectional perspectives. In Section 3, four chapters examine the intercorporeal nature of meaning-making during human interaction. Section 4 then presents three chapters that explore the intercorporeal nature of multi-agent interactions and the role that non-animate bodies (i.e., objects) play in such interaction. Throughout all the chapters, the authors work to integrate research in their specific discipline into the larger, transdisciplinary notion of intercorporeality. This collection provides an indisputably unique perspective on bodies-in-interaction, while simultaneously offering an interdisciplinary way forward in contemporary scholarship on bodies, meaning, and interaction. "--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Interaktion; Objekt; Körper; Mensch